2021
DOI: 10.1037/tep0000301
|View full text |Cite
|
Sign up to set email alerts
|

Pass rates on the Examination for Professional Practice in Psychology (EPPP) according to demographic variables: A partial replication.

Abstract: The Examination for Professional Practice in Psychology (EPPP) is a licensure requirement across 62 psychology boards. However, psychometric support for the EPPP consists primarily of content validation studies. Recent data from a large New York sample indicated that EPPP performance and pass rates differed according to demographic variables, with Black and Hispanic applicants failing at much higher rates than Asians and Whites, men failing more than women, and PsyDs failing more than PhDs. In order to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The current EPPP, which uses the same methods as does Part 2, evidences significantly lower pass rates for underrepresented Black or African American and Hispanic applicants than does the dominant majority (Sharpless, 2019a(Sharpless, , 2019b. In light of such findings, Turner and colleagues' (2021) continued defense of nonrepresentative early adopter jurisdictions for norming suggests entrenched processes and procedures for sustaining racial inequities that contribute to systemic racism.…”
mentioning
confidence: 95%
“…The current EPPP, which uses the same methods as does Part 2, evidences significantly lower pass rates for underrepresented Black or African American and Hispanic applicants than does the dominant majority (Sharpless, 2019a(Sharpless, , 2019b. In light of such findings, Turner and colleagues' (2021) continued defense of nonrepresentative early adopter jurisdictions for norming suggests entrenched processes and procedures for sustaining racial inequities that contribute to systemic racism.…”
mentioning
confidence: 95%
“…Extant literature points to recurrence of constriction at a subsequent point in the training-to-workforce pipeline: the requisite national licensure exam (Sharpless, 2019(Sharpless, , 2021Sharpless & Barber, 2009). Many issues have been raised regarding the Examination for Professional Practice in Psychology (EPPP) and its validity (Callahan et al, 2020(Callahan et al, , 2021DeMers, 2009;DiLillo & Tremblay, 2009;Erikson Cornish & Smith, 2009;Ryan & Chan, 1999), but one particularly problematic concern is the role of the EPPP in furthering diversity constriction occurring at the precipice of entering the profession.…”
Section: Figurementioning
confidence: 99%
“…Many issues have been raised regarding the Examination for Professional Practice in Psychology (EPPP) and its validity (Callahan et al, 2020(Callahan et al, , 2021DeMers, 2009;DiLillo & Tremblay, 2009;Erikson Cornish & Smith, 2009;Ryan & Chan, 1999), but one particularly problematic concern is the role of the EPPP in furthering diversity constriction occurring at the precipice of entering the profession. Research has consistently indicated that fail rates of first-time EPPP test takers differ significantly by racial/ ethnic status, with a much higher rate of failure being found among underrepresented Black/African American (23.33%) and Hispanic/ Latinx (18.60%) applicants as compared to Asian (3.33%) or White (5.75%) applicants (Sharpless, 2019(Sharpless, , 2021. Our findings, coupled with research indicating the significant barriers occurring at the undergraduate psychology and licensure levels, help to identify which areas of the training-to-workforce clinical psychology diversity pipeline are laudable (i.e., internship match) and which areas are in dire need of improvement (i.e., doctoral recruitment and admissions; licensure examination).…”
Section: Figurementioning
confidence: 99%
“…of everyone seeking licensure in the US and Canada. Concerns regarding the construct-irrelevant variance (i.e., influence of demographic variables) on pass rates for the EPPP have been raised (Sharpless, 2019a(Sharpless, , 2019b, with results suggesting that being Black or Hispanic is associated with increased likelihood of failing the exam during the first attempt compared to those who are White or Asian. Thus, it is critical that our field-which emphasizes training in creating and evaluating psychometrically sound instruments (e.g., assessment psychometrics is an area of core competency for professional psychologists, Kaslow et al, 2009)-use acceptable practice for creating and validating a test relatively free from bias.…”
Section: Unrepresentative Sampling For Normsmentioning
confidence: 99%